2001
DOI: 10.1152/ajprenal.2001.281.3.f454
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cations, anions, and weak base quinine with rat renal cation transporter rOCT2 compared with rOCT1

Abstract: The rat organic cation transporter (rOCT)-2 was characterized by electrical and tracer flux measurements compared with rOCT1. By applying choline gradients to voltage-clamped Xenopus oocytes expressing rOCT2, potential-dependent currents could be induced in both directions. Tracer flux measurements with seven organic cations revealed similar Michaelis-Menten constant values for both transporters, with the exception of guanidine. In parallel experiments with rOCT2 and rOCT1, inhibition of tetraethylammonium tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
146
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(162 citation statements)
references
References 36 publications
14
146
1
1
Order By: Relevance
“…A choline K m value for hOCT2 of 102 Ϯ 80 M was also found (data not shown). These values are similar to respective reported values for the transporters (17,27,39).…”
Section: Characterization Of Choline Transport By Octs-oocytessupporting
confidence: 91%
See 1 more Smart Citation
“…A choline K m value for hOCT2 of 102 Ϯ 80 M was also found (data not shown). These values are similar to respective reported values for the transporters (17,27,39).…”
Section: Characterization Of Choline Transport By Octs-oocytessupporting
confidence: 91%
“…It has also been shown that rOCT1 and rOCT2 are both effectively inhibited by TMA, but rOCT3 is not (14,15,22). Guanidine could prove to be a substrate with markedly different affinities for rOCT1 (K m ϭ 172 Ϯ 57 M), rOCT2 (K m ϭ 1,660 Ϯ 670 M), and rOCT3 (K m ϭ 35 M); however, the K m value for rOCT3 was determined in transfected HeLa cells and not Xenopus oocytes (14,27). In support of the present hypothesis that OCTs expressed in CP function in the regulation of free choline in CSF, we and others (17, 25, 28 -30) have found that choline inhibits uptake mediated by rOCT2 and rOCT3 and that choline itself is transported by rOCT1 and hOCT2.…”
mentioning
confidence: 99%
“…Rat OCT1 is much less sensitive to inhibition by corticosterone (IC 50 ϭ 150 M) than are OCT2 (IC 50 ϭ 0.48 -4 M) and OCT3 (IC 50 ϭ 0.3-4.9 M) (Wu et al, 1998;Arndt et al, 2001;Shang et al, 2003;Volk et al, 2003). Estradiol 17-␤ is a more potent inhibitor of OCT3 (IC 50 ϭ 1.1 M) than of OCT2 (IC 50 ϭ 85 M) (Wu et al, 1998).…”
Section: [ 3 H]-histamine Uptake Acutely Prepared 3v-mh Minces Accumumentioning
confidence: 99%
“…Based on studies of peripheral tissues, all three OCTs transport 5-HT, dopamine, and norepinephrine (Busch et al, 1996;Grundemann et al, 1998;Koepsell et al, 2003) and are acutely inhibited by corticosterone (Wu et al, 1998;Arndt et al, 2001). OCT expression has been detected in neurons and cultured glial cells (Russ et al, 1996;Busch et al, 1998;Vialou et al, 2004), and physiological roles for OCTs in the brain have been suggested (Kristufek et al, 2002;Kitaichi et al, 2003;Vialou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The transport mediated by rOCT1 has been characterized as electrogenic, independent of Na ϩ and pH, and bidirectional by radioactive tracer flux measurements with oocytes from Xenopus laevis expressing rOCT1 (17). rOCT1 can translocate organic cations like TEA ϩ and choline (18), cathecolamines (19), and nucleosides like 2Ј-deoxytubercidin (20), whereas cations like tetrapentylammonium (TPA ϩ ) and cyanine 863 are nontransported inhibitors of the transporter (21). For this transport protein 12 transmembrane domains, a large hydrophilic extracellular loop between the first and the second predicted transmembrane domain and an intracellular localization of the Nand C-termini have been described (22).…”
mentioning
confidence: 99%